2015
DOI: 10.1097/pgp.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor of the Placenta

Abstract: Inflammatory myofibroblastic tumor has been described in a wide variety of anatomic sites, although in the gynecologic tract, it has mostly been documented in the uterus, and has never been described in the placenta. Two patients presented with well-circumscribed placental masses that showed classic histologic features of inflammatory myofibroblastic tumor including a proliferation of myofibroblastic cells, a mixed inflammatory infiltrate, and a myxoid background. One case was positive by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Examination of the placenta showed no involvement by tumor in one patient, whereas details were not available for the other. Decidual-like change in inflammatory myofibroblastic tumors was previously reported by Banet et al 26 who described two cases arising in the placenta. Both tumors were confined to the placental disc and had morphologic features consistent with an inflammatory myofibroblastic tumor, although one was ALK-negative.…”
Section: Discussionsupporting
confidence: 59%
“…Examination of the placenta showed no involvement by tumor in one patient, whereas details were not available for the other. Decidual-like change in inflammatory myofibroblastic tumors was previously reported by Banet et al 26 who described two cases arising in the placenta. Both tumors were confined to the placental disc and had morphologic features consistent with an inflammatory myofibroblastic tumor, although one was ALK-negative.…”
Section: Discussionsupporting
confidence: 59%
“…In this current case, the vicinity of the tumor demonstrated flat epithelial atypia in lobular units and PASH in the surrounding stroma. There are only a few case reports in the literature with ER and PR receptor expression in IMT (11,12). Banet et al (11) reported 2 IMT cases within the placenta, one of which showed patchy expression for PR receptor without ALK immunoreactivity, as well as gene rearrangement (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the female genital tract, uterine‐based lesions are the most common, with tumors more often arising in the corpus than the cervix 80‐83 . Rare cases involve the placenta 84‐90 and ovary, 91 the former likely uterine in origin based on short tandem repeat genotyping 89 . Given the risk of local recurrence and rare metastasis, IMT is considered to have intermediate biological potential regardless of primary site.…”
Section: Inflammatory Myofibroblastic Tumormentioning
confidence: 99%
“…Patients may be asymptomatic or present with abnormal uterine bleeding, abdominal or pelvic pain, and/or an abdominal or pelvic mass 80‐83,92‐104 . Some cases are associated with pregnancy and are often discovered incidentally at the time of delivery within the placental disk, fetal membranes, or a mass separate from the placenta and uterus 84‐90 . Uterine IMTs have a mean size of 6.3 (range, 1‐20) cm 22,80‐83,92,94‐96,100‐102,104 .…”
Section: Inflammatory Myofibroblastic Tumormentioning
confidence: 99%